Ще раз про ямні поховання ранньосередньовічного верхньосалтівського катакомбного могильника - Аксьонов, В.С. (Археологія, 2023)
У статті зроблено спробу довести, що катакомби
та розташовані поряд із ними поховання дітей в
окремих ґрунтових ямах різної конструкції являють
собою єдиний поховальний комплекс, що належить
представникам однієї родини. Поховання дітей в
окремих могилах зумовлене нестачею вільного місця для них у поховальній камері катакомби та неможливістю з об’єктивних причин викопати для
них окрему катакомбу. On the site of the main Verkhnii Saltiv catacomb burial ground, explored in 1984—1989 by the expedition of the Kharkiv
Historical Museum, in addition to 76 catacomb burials, 17 burials in pits of various designs were found (nine in simple soil
pits and eight in pits with lining). All studied pit burials belonged to children and adolescents, 14 of them were associated with
specific catacombs, because they were located in the immediate vicinity of the dromoi of the catacombs or were let into their
filling (burials nos. 13; 15 — catacombs nos. 72; 74). The inventory of the studied pit burials did not differ in composition,
typology and quantitative indicators from the inventory that accompanied the bones of children from the burial chambers of the
catacombs of the same burial ground. This inventory serves as an indicator of a certain property and social status of families
whose members were children buried in pit graves. The planigraphy and inventory of pit burials allows stating that the children
burials and the catacombs next to which they are located should be considered as a single burial complex that belonged to close
relatives or members of the same family. At the same time, six of the nine catacombs (nos. 30; 39; 41; 44; 51; 52) with which
the pit burials are associated had burial chambers located longitudinally in relation to the dromos, differing in small sizes and
containing the remains of two or three deceased. The burial chambers of the T-shaped catacombs (nos. 72; 73; 74), which are
somewhat larger, also contained three or four human skeletons. The burial of children in separate pits of various designs is due
to the lack of free space for new burials in the burial chambers of the catacombs associated with them. It was impossible because
of some objective reasons (unfavorable season, lack of resources and time, nature of death, etc.) to dig new catacombs for child
burials.